Hydrogen behavior in bimetallic systems:permeation through thin metal films - Glazunov, G.P.; Volkov, E.D.; Hassanein, A. (Вопросы атомной науки и техники, 2000)
The hydrogen permeation performances are presented for micron Mo, Ti, Nb, Zr, Cr, Ni, Cu, CuPd, TiN, and stainless steel films deposited on palladium from arc sputtered cathodes. Some physical mechanisms explaining anomalies behavior in above mentioned systems are suggested. In particular, it is shown that extreme high hydrogen permeability in the Mo-Pd system is caused by enhancing of diffusion coefficient in the system with a large number of connected pores. Also the possible use of such systems for an active control of recycling and erosion processes are considered. In the frame of non-ideal plasma theory the mechanism is suggested of hydrogen high content (clusters) formation as the result of hydrogen plasma phase transitions in metal. The small hydrogen clusters can be condensed in metal lattice. The arising of the large ones is more probably around defects and in submicro- and micro-pores appearing under, for example, plasma or energetic particle irradiation.